Bimbingan Belajar Literasi Dan Numerasi Bagi Anak Tingkat SD Dan SMP Di Desa Nagori Sihalpe Kec. Haranggaol Horison - Kammer Tuahman Sipayung; Novani Saragi; Santa Hoky Hutagalung; Desi Muliani Saragih; Rutmayana Br. Sianturi (Lembaga Pengembangan Kinerja Dosen, 2024)
Community Service (PkM) Faculty of Teacher Training and Education (FKIP) HKBP Nomensen University Medan is a service program carried out by a team of students and DPL lecturers with the title